Aspirin for Primary Prevention of Cardiovascular Disease: What We Now Know - Weisman, Steven M; Angiolillo, Dominick J (Journal of Cardiology and Cardiovascular Medicine, 2024)
Cardiovascular disease (CVD), including coronary artery disease and stroke, is the leading cause of death worldwide. Advances in primary and secondary prevention of CVD have improved patient prognoses and outcomes, however, it is imperative that the clinician and patient engage in early risk factor screening and preventive management of modifiable risk factors for CVD. In addition to blood lipid and blood pressure lowering medications, aspirin has been a long-standing therapy targeted to the prevention of CVD based on its antiplatelet and anti-inflammatory activity. However, recent articles and reports on updates to clinical guidelines for the primary prevention of CVD have resulted in confusion about aspirin recommendations. This review aims to assess the latest guidance on aspirin in CVD prevention and how to identify appropriately at-risk patients who may benefit from low-dose aspirin therapy as part of their CVD preventive healthcare choices. Additionally, this review will provide practical application guidance about clinician-patient conversations to clearly explain the benefits and risks of aspirin use and ensure a patient-centric decision to initiate aspirin therapy.